SUBKULTUR ANAK MUDA DALAM IKLAN KOPI DI INDONESIA: KAJIAN SEMIOTIKA ROLAND BARTHES - Aling Madani; Jatiwuni Ambarwati (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
The current trend and existence of coffee continues to develop into a part of the lifestyle of youth. Therefore, coffee products on the market are increasingly varied with various advertising strategies. Various advertising themes related to youth activities and identities are used to reach their target market. This study is a semiotic analysis that aims to describe the symbols and cultural styles of youth in coffee advertisements in Indonesia by using the concept of youth subculture. The focus of this research is the meaning of youth's visual signs represented through coffee advertisements in Indonesia. This study uses a qualitative method. The data collection technique was carried out by observing instant coffee advertisement impressions in Indonesia in the last five years, including the Torabika for the Gilus Mix variants (2021) and Cappuccino (2019), Top Coffee for the Gula Aren variant (2020), Neo Coffee version of Lucas (2019) and Tiramisu (2021), and Good Day (2018). Roland Barthes' semiotic analysis is used in this study to show the sign meanings in the coffee advertisement through the stages of denotative, connotative, and mythical meanings. The results of the study show that these coffee advertisements generate units of denotation, connotation, and myth which then represent the lifestyle of the youth subculture. It exists in various aspects and refers to urban youth culture with urban cultural influences as reflected in clothing/fashion styles, distinctive music, and entertainment activities.